PEMETAAN TREN PENELITIAN LITERASI MATEMATIKA MELALUI SYSTEMATIC LITERATURE REVIEW DAN ANALISIS BIBLIOMETRIK - Abdul Rahman; Usman Mulbar (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2026)
Mathematical literacy is an essential 21st-century competency that plays a crucial role in supporting individuals’ abilities to reason, solve problems, and make data-driven decisions across various real-life contexts. Along with the growing global attention to mathematical literacy, particularly through international assessments such as the PISA, research in this field has expanded rapidly in both quantity and scope. However, findings reported across different journals remain fragmented, highlighting the need for a systematic mapping to obtain a comprehensive overview of research trends, distributions, and future directions in mathematical literacy studies. This study aims to examine the relevance of mathematical literacy as a focus for future research, identify research trends and distributions, and explore the theoretical and practical implications for subsequent studies. The research employed a Systematic Literature Review combined with bibliometric analysis of 268 Scopus-indexed articles published up to December 15, 2025. The literature selection process followed the PRISMA framework, while bibliometric mapping and visualization were conducted using VOSviewer software. The results indicate a significant upward trend in publications since 2016, peaking in the 2023–2025 period, suggesting that mathematical literacy remains a highly relevant and prominent topic in mathematics education research. Geographically, Indonesia emerged as the largest contributor and a central hub in international research collaboration networks. Keyword co-occurrence analysis revealed the dominance of themes related to mathematical literacy, students, gender differences, psychology, PISA, and controlled studies. Nevertheless, notable research gaps persist, particularly regarding the integration of digital learning media. These findings provide important theoretical and practical foundations for the advancement of future research and instructional innovations in mathematical literacy.